1190 Activated Protein C Alters Neutrophil Reactive Oxygen Intermediates in Preterm Neonates. (October 2012) - Eliwan, HO; Watson, W; O'Neill, A; O'Hare, F; Molloy, EJ
Abstract : Background: Inflammation and infection are important aetiological factors in development of preterm birth. Inflammation is associated with many disorders of preterm infants including periventricular leukomalacia, chronic lung disease and necrotising eneterocolitis. Aims: To compare neutrophil and monocyte responses to lipopolysaccaride (LPS) +/-APC (activated protein c) stimulation in preterm neonates < 32 weeks gestation with adults controls. Methods: Whole blood was incubated with LPS +/-APC and Toll-like receptor4 (TLR4), CD11b expression, and reactive oxygen intermediate (ROI) release from neutophils and monocytes was examined by flow cytometry. Results: Both adults (n=15) and preterm neonates (n=30) had significantly increased LPS induced neutrophil CD11b expression but preterms are less responsive than adults. There was a significant increase in neutrophil ROI in response to LPS in adults and preterm neonates on day 1 and this was significantly reduced by APC There was significant higher baseline and endotoxin response of monocyte ROI in preterm neonates compared to adult (p<0.05). However APC had not reduced this response. Conclusion: Increased ROI release may mediate tissue damage and was significantly increased in preterm neonates and adults. APC reduced LPS-induced neutrophil ROI release. This may benefit preterm neonates at high risk of multiorgan inflammatory disorders but they are at high risk of haemorrhage. Further examination of APC mutants with anti-inflammatory but decreased anticoagulant properties is merited.